Modelling and Control of the Modular Multilevel Converter in Back to Back Configuration for High Power Induction Machine Drives - Diaz-Diaz, M (IEEE Computer Society, 2016)
Drives based on modular multilevel topologies are the next generation of high-power/voltage converters. In this paper, the Modular Multilevel Converter model is extended to the Back to Back scheme, allowing its control as an unique system, instead two separated converters. Additionally, the proposed control strategy is able to regulate the ac ports and to perform the voltage balancing in both converters by using circulating currents and common mode voltage, providing independence between the converters and the ac ports. Extensive computer simulation and a laboratory prototype of a Modular Multilevel Converter with eighteen power cells feeding an induction machine validate the effectiveness of the presented control algorithm. © 2016 IEEE.